2021
DOI: 10.1080/20964129.2021.1929502
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of urban greenery using hemisphere-view panoramas with a green cover index

Abstract: Quantification of urban greenery using hemisphere-view panoramas with a green cover index Yonglin Zhang a (0000-0001-5432-8800), Shanlin Li b (0000-0002-0261-7106), Xiao Fu a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…The results of the study showed that the panorama technology can comprehensively measure the street greening distribution information and guide the planning and management of the urban greening landscape [37]. Several studies have also explored the application of panorama techniques in the evaluation of different types of landscapes [1,28,29,38,39]. For example, Zhang et al used panoramic techniques to present natural landscape scenes to study participants' beauty evaluations of different landscape features (e.g., water, vegetation).…”
Section: Application Of Panoramic Techniques In Landscape Perception ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that the panorama technology can comprehensively measure the street greening distribution information and guide the planning and management of the urban greening landscape [37]. Several studies have also explored the application of panorama techniques in the evaluation of different types of landscapes [1,28,29,38,39]. For example, Zhang et al used panoramic techniques to present natural landscape scenes to study participants' beauty evaluations of different landscape features (e.g., water, vegetation).…”
Section: Application Of Panoramic Techniques In Landscape Perception ...mentioning
confidence: 99%
“…For example, Zhang et al used panoramic techniques to present natural landscape scenes to study participants' beauty evaluations of different landscape features (e.g., water, vegetation). The results of the study showed that the panorama technique could provide more diverse scene information, enabling participants to more accurately evaluate the impact of different landscape features on beauty [28,29,38]. Additionally, Qin et al delved into the panorama technique's application in natural landscape perception.…”
Section: Application Of Panoramic Techniques In Landscape Perception ...mentioning
confidence: 99%
“…Various evaluation indices have been proposed to quantify vegetation, including the normalized difference vegetation index (NDVI), leaf area index, living vegetation volume, green cover index, green visual ratio, and fractional vegetation cover [24][25][26][27][28][29]. NDVI is derived from a combination of linear and non-linear spectral bands, allowing it to capture the spatiotemporal growth and distribution of vegetation effectively.…”
Section: Introductionmentioning
confidence: 99%